Can a Repeated Opt-Out Reminder remove hypothetical bias in discrete choice experiments? An application to consumer valuation of novel food products - Mohammed H. Alemu; Søren Bøye Olsen (University of Copenhagen, Department of Food and Resource Economics (IFRO), 2017)
Recent papers have suggested that use of a so-called Repeated Opt-Out Reminder (ROOR) might mitigate hypothetical bias in stated Discrete Choice Experiments (DCE), but evidence so far has only been circumstantial. We provide the first comprehensive test of whether a ROOR can actually mitigate hypothetical bias in stated DCE. The data originates from a field experiment concerning consumer preferences for a novel food product made from cricket flour. Utilizing a between-subject design with three treatments, we find significantly higher marginal willingness to pay values in hypothetical than in nonhypothetical settings, confirming the usual presence of hypothetical bias. Comparing this to a hypothetical setting where the ROOR is introduced, we find that the ROOR effectively eliminates hypothetical bias for one attribute and significantly reduces it for the rest of the attributes. Our results further suggest that these reductions of hypothetical bias are brought about by a decrease in the tendency to ignore the price attribute.
Keywords: C12; C13; C83; C93; D12; O13; Q01; Q11; Q13; Q18; 330; Hypothetical bias; novel food; repeated opt-out reminder; willingness to pay